2009
DOI: 10.1111/j.1469-7580.2009.01155.x
|View full text |Cite
|
Sign up to set email alerts
|

Fibre type composition of the human psoas major muscle with regard to the level of its origin

Abstract: The aim of our study was to explore the fibre type composition of the human psoas major muscle at different levels of its origin, from the first lumbar to the fourth lumbar vertebra, and to compare the muscle fibre size and distribution of different fibre types between levels with respect to its complex postural and dynamic function. Muscle samples were collected from 15 young males (younger than 35 years). Serial transverse sections (5 lm) of the samples were cut by cryomicrotome. Type I, IIA and IIX muscle f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 32 publications
1
43
1
2
Order By: Relevance
“…As described earlier, trunk muscles have a critical role in the maintenance of stability and balance when performing movements with the extremities (Andersen et al, 1988), and a strong and stable trunk provides a solid foundation for the torques generated by the limbs (Behm and Anderson, 2006;Kibler et al, 2006). Among the muscle groups located in the trunk, PM is the only muscle that connects the lumber spine and lower limbs (Arbanas et al, 2009). Taking this into account together with previous findings on sex differences in muscular distribution (Abe et al, 2003;Janssen et al, 2000) and strength (Bishop et al, 1987), therefore, the greater PM CSA in the boys compared to the girls might be assumed to be a functional requirement associated with greater development in the muscle mass and strength capability of the upper extremity and trunk.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…As described earlier, trunk muscles have a critical role in the maintenance of stability and balance when performing movements with the extremities (Andersen et al, 1988), and a strong and stable trunk provides a solid foundation for the torques generated by the limbs (Behm and Anderson, 2006;Kibler et al, 2006). Among the muscle groups located in the trunk, PM is the only muscle that connects the lumber spine and lower limbs (Arbanas et al, 2009). Taking this into account together with previous findings on sex differences in muscular distribution (Abe et al, 2003;Janssen et al, 2000) and strength (Bishop et al, 1987), therefore, the greater PM CSA in the boys compared to the girls might be assumed to be a functional requirement associated with greater development in the muscle mass and strength capability of the upper extremity and trunk.…”
Section: Discussionmentioning
confidence: 95%
“…However, Alway et al (1989) reported that, for biceps brachii, the ratio of type II fiber area to LBM was higher in male bodybuilders than in female bodybuilders, but the corresponding ratio for type I fibers was similar between the two groups. Arbanas et al (2009) indicated that the human psoas major muscle has a predominance of type IIA fibers. Considering these findings, therefore, the possible difference in the size of type II fibers between the boys and girls might also be a reason for the sex difference observed in PM CSA/ LBM 2/3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psoas is the main flexor of the hip and also provides postural support of the lumbar spine, sacroiliac, and hip joints. The fibre type is mixed (40% type I, 50% type IIa, and 10% type IIx) with the 60:40 predominance of fast fibres providing for psoas dynamic and postural functions 8, 9. However, as Rutter et al 7.…”
mentioning
confidence: 99%
“…51 The recruitment pattern involves the concepts of timing patterns and timing of onset; to maintain stability, the muscles should activate at the right time and sequence, 5 and recruitment patterns are modulated according to the demands placed on the lumbar spine. 53,82 Other characteristics related to joint stability reported in the literature include biomechanical characteristics (e.g., local or deep muscles that have their origin and insertion close to a joint, short moment arms 78,79 ) and anatomical/physiological characteristics (e.g., high proportion of type I fibres, large PCSA 29,79 ). However, these characteristics were less often reported and the articles rarely provided supporting evidence for them.…”
Section: Force Closurementioning
confidence: 99%